2014
DOI: 10.1017/hia.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Serendipity: Conducting Research on Social History in Ghana’s Archives

Abstract: This report provides practical ideas and methodological warnings regarding the use of Ghanaian archives for the writing of social history.Résumé : Ce rapport propose des idées pratiques ainsi que des suggestions méthodo-logiques au sujet de l'emploi des archives du Ghana pour écrire l'histoire sociale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Only rather rarely have scholars emphasized the importance of carrying out research in smaller and less-explored archives 6 . For colonial archives, recent scholarly work has pointed to possibilities in Uganda, Ghana and Mali (Mann 1999; McConnell 2005; Ntewusu 2014; Rodet 2010). We have already noted the importance of vital new insights on regional archives relating to issues of custodial cultures and material challenges, but the question of their research potential remains unaddressed; in other words, it is mostly unclear what these archives are able to provide for historical research.…”
Section: Postcolonial African Archival Pessimism: Another Obstacle Fo...mentioning
confidence: 99%
“…Only rather rarely have scholars emphasized the importance of carrying out research in smaller and less-explored archives 6 . For colonial archives, recent scholarly work has pointed to possibilities in Uganda, Ghana and Mali (Mann 1999; McConnell 2005; Ntewusu 2014; Rodet 2010). We have already noted the importance of vital new insights on regional archives relating to issues of custodial cultures and material challenges, but the question of their research potential remains unaddressed; in other words, it is mostly unclear what these archives are able to provide for historical research.…”
Section: Postcolonial African Archival Pessimism: Another Obstacle Fo...mentioning
confidence: 99%
“…On the principled side, the religious actors acknowledged the restrictive measures as steps in the right direction since they know that the medical structures, facilities and personnel of virtually every African state were inadequate, fragile and poor. 72 It is widely known that most of the trained medical personnel in Africa migrate in deluge to other continents for greener pastures, 73 person nel on the continent. For instance, the General Medical Council of Britain recently revealed that 805 Nigerian medical doctors were licensed in the United Kingdom between July and December 2021.…”
Section: Religious Responses To the Regulationsmentioning
confidence: 99%
“…The use of the archives in conducting social research is quiet revealing and to put it more succinctly Ntewusu (2014) posited that conducting social history in Ghana's archives is serendipity. This he indicated that the archives provides materials or resources that are academically stimulating and revealing but also cautioned of the enormous challenges confronting the archives which hinders effective research process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As valuable as the archives are, they were not without limitations. Ntewusu (2014) outlined a few of these limitations to include the physical conditions of the files, classification, accessibility and terminology. The physical conditions of most of the files in the archives of Ghana are in a deplorable state.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation